Can Trade with the People's Republic of China be an Engine of Growth for Developing Asia? - Donghyun Park; Kwanho Shin (Asian Development Bank (ADB), 2009)
The recession in the United States in the wake of the global financial crisis has had a pronounced negative impact on developing Asia's exports and growth. As a result, developing Asian countries are increasingly looking to the People's Republic of China (PRC) as a new source of demand and growth. The central objective of this paper is to empirically assess whether trade with the PRC can become an engine of growth for developing Asia. To do so, we examine the structure of PRC's trade with developing Asia, in particular the relative shares of parts and components versus final goods in its imports from the region. Our most significant result is that the share of final goods in the PRC's imports from East and Southeast Asia has been rising while the share of parts and components has been falling, suggesting that the PRC is becoming more of a consumer and less of an assembler. This provides ground for optimism about the prospects of trade with the PRC as a source of resilience against extra-regional demand shocks in the short run and an additional source of growth in the long run.
hdl:11540/4186
Keywords: F10; F14; F15; 330; China; Asia; engine; recovery; growth; trade; production fragmentation